Beyond mastery: jazz, gender and power in postapartheid South Africa - Williams, Ulagh (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
This dissertation studies the musical lives of seven South African women who have built highprofile national and international careers as jazz musicians. Empirically it records self-reported experiences and actions that they have identified as relevant to their success within a notoriously patriarchal field. Drawing on feminist research methods and Interpretative Phenomenological Analysis the dissertation strives to develop an empathic yet critical epistemological framework attuned to the complexities of their lived experiences as women and as jazz musicians. Theoretically it investigates the power relations at play in the myriad ways they negotiate or have been impelled to negotiate gender and patriarchy as musicians. Chapter one draws attention to the ubiquity of patriarchy in South African and international jazz culture, and highlights the research participants' numerous successes to date as performers, educators, composers, and bandleaders. Chapter two positions this study in relation to cognate work in South African jazz studies, international feminist jazz studies and feminist phenomenology. Chapters three to five successively consider the participants' early enculturation as musical and gendered subjects, their agentic responses to structures of patriarchy and/or race as emerging and established professionals, and the ways these experiences have found expression in some of their musical utterances as performers and composers. Fusing art and activism, the participants challenge and transcend masculinist discourses of mastery that still dominate South African jazz as a field of production and aesthetic practice.
Keywords: Feminist theory; Women jazz musicians -- South Africa; Music Instruction and study; Interpretative phenomenological analysis; Control (Psychology); Male domination (Social structure)